Let's solve the equation step by step:
Given: \[ 4(x - 6) + 2 = 6x - 8 \]
-
Distribute the \(4\) on the left side: \[ 4x - 24 + 2 = 6x - 8 \]
-
Combine like terms on the left side: \[ 4x - 22 = 6x - 8 \]
-
Now, we want to isolate \(x\). First, let's move \(4x\) to the right side: \[ -22 = 6x - 4x - 8 \]
-
Simplify the right side: \[ -22 = 2x - 8 \]
-
Next, add \(8\) to both sides to isolate the term with \(x\): \[ -22 + 8 = 2x \] \[ -14 = 2x \]
-
Finally, divide both sides by \(2\) to solve for \(x\): \[ x = -7 \]
So, the solution to the equation is: \[ x = -7 \]